Cell surface-localized imaging and sensing. (9th April 2021) - Jia, Hao-Ran; Zhu, Ya-Xuan; Duan, Qiu-Yi; Wu, Fu-Gen
Abstract : We present a comprehensive review on the advancements in cell surface modification strategies and their applications in cell surface-localized imaging and sensing. Abstract : Systematically dissecting the molecular basis of the cell surface as well as its related biological activities is considered as one of the most cutting-edge fields in fundamental sciences. The advent of various advanced cell imaging techniques allows us to gain a glimpse of how the cell surface is structured and coordinated with other cellular components to respond to intracellular signals and environmental stimuli. Nowadays, cell surface-related studies have entered a new era featured by a redirected aim of not just understanding but artificially manipulating/remodeling the cell surface properties. To meet this goal, biologists and chemists are intensely engaged in developing more maneuverable cell surface labeling strategies by exploiting the cell's intrinsic biosynthetic machinery or direct chemical/physical binding methods for imaging, sensing, and biomedical applications. In this review, we summarize the recent advances that focus on the visualization of various cell surface structures/dynamics and accurate monitoring of the microenvironment of the cell surface. Future challenges and opportunities in these fields are discussed, and the importance of cell surface-based studies is highlighted.